Enhancing student engagement through practice experience in social work education: The Social Work Studio - Campbell, Alan (2012)
It can sometimes be difficult to engage students in 'real life experiences' within the classroom. In one Bachelor of Social Work program, the development of a Social Work Studio (the Studio) has provided students with opportunities to engage in simulated social work practice in a safe and supportive environment. This article reports on a small exploratory study of students' responses to a survey that sought their views and reactions to the development of this Studio initiative. Findings were analysed from a sociocultural perspective. They indicate that students' responses to the development of the Studio reflect their emerging constructions of the cultural world of social work.